PERSEPSI SISWA DAN HAMBATAN SEKOLAH TERHADAP POTENSI PENGGUNAAN MEDIA DIGITAL DI SEKOLAH DASAR - Afif Fawaz Arkan; Rachmat Imam Muslim & Meilan Tri Wuryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The digital technology transformation has brought significant changes to the field of education, including at the elementary school level. This study aims to explore students’ perceptions and the challenges faced by schools in utilizing digital media for learning at SDN 01 Plelen, which his located in a rural area with limited technological infrastructure. This research method uses a descriptive qualitative approach, data was collected through observation, questionnaires, and interviews with class II students and teachers. The results show that the majority of students demonstrate enthusiasm and a positive perception toward digital media, particularly in terms of motivation and understanding of the material. Meanwhile, teachers acknowledge that digital media can enhance the effectiveness of learning but still face challenges such as limited devices, internet access, and the need for technical training. This study recommends improving infrastructure, providing teacher training, and ensuring ongoing technical support to optimize the implementation of digital media in elementary schools, especially in areas with limited access to technology.